Loculated pneumothorax due to a rare combination resulting in an interesting chest radiograph. (24th February 2016) - Isaac, Barney Thomas Jesudason; Samuel, Johnson Thamarathu; Mukherjee, Dipak K.; Pittman, Marcus
Abstract : Abstract: A 35 years old man presented with acute onset left sided pleuritic chest pain and shortness of breath. On evaluation, he was found to have an interesting chest radiograph which showed a loculated pneumothorax with collapse of the left upper lobe and lingula but fully expanded left lower lobe. He is a known asthmatic who had allergic broncho pulmonary aspergillosis (ABPA) previously with left upper lobe and lingular collapse secondary to mucous plugging. This resolved on treatment with steroids and itraconazole. An interesting combination of events is proposed to explain the current presentation. CT scan chest and blood tests confirmed this sequence of events. He was appropriately treated resulting in complete clinical and radiological recovery. The events leading to the presentation and the likely physiological background for this interesting chest radiograph are discussed.